2018
DOI: 10.3892/mmr.2018.8604
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein induces choriocarcinoma cell apoptosis in a dose-dependent manner via the mitochondrial apoptotic pathway

Abstract: Choriocarcinoma is a malignant gestational trophoblastic disease and relapse or drug resistance occurs in ~25% of gestational trophoblastic tumors. Cell apoptosis serves a role in the progression from hydatidiform mole to persistent gestational trophoblastic disease. It has been demonstrated that daidzein [7‑hydroxy‑3‑(4‑hydroxyphenyl)‑4H‑chromen‑4‑one] may induce apoptosis in a number of cancer types via the mitochondrial apoptotic pathway by altering the B‑cell lymphoma (Bcl)‑2/Bcl‑2 associated X, apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This could be because soy milk is rich in isoflavones, and may induce apoptosis unselectively. The present toxicity effect of coumestrol, daidzein and genistein to cancer cells was in good agreement with some previous studies which satisfactorily showed that high potential of phytoestrogens in killing cancer cells by the induction of apoptosis in prostate, hepatocellular carcinoma, bladder and colon cancer with various mechanism actions involved [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…This could be because soy milk is rich in isoflavones, and may induce apoptosis unselectively. The present toxicity effect of coumestrol, daidzein and genistein to cancer cells was in good agreement with some previous studies which satisfactorily showed that high potential of phytoestrogens in killing cancer cells by the induction of apoptosis in prostate, hepatocellular carcinoma, bladder and colon cancer with various mechanism actions involved [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies indicate that DZ induces considerable anticancer action via the development of programmed cell death [ 45 ]. The compound has been reported to trigger apoptosis via the mitochondrial apoptotic pathway in various cancer types, such as breast cancer, gastric carcinoma, and hepatic cancer, by optimizing the Bcl-2/Bax ratio to activate the caspase cascade [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many natural and synthetic substances have been tested in the placental choriocarcinoma cell line. Some of them are daidzein, neuropeptide Y, fungicide ziram (CHEN et al, 2017;MATIĆ et al, 2017;ZHENG et al, 2018). There is an even larger number of studies on the influence of steroid hormones and their derivatives on the JEG-3 cell line, but also on the modulation of their synthesis (LONG et al, 1998;HONKISZ and WÓJTOWICZ, 2015;XU et al, 2019).…”
Section: Introductionmentioning
confidence: 99%